OP99 Hypertensive disorders in pregnancy and childhood diagnosis of asthma. (3rd September 2019) - Kelly, L; Barrett, P; McCarthy, F; Khashan, AS
Abstract : Background: Hypertensive disorders of pregnancy (HDP), the most common pregnancy complication, have been linked to childhood morbidity. Few studies have investigated the relationship between HDP and asthma in the offspring, with existing research showing conflicting results.The primary aim of this study was to explore the association between HDP and the development of asthma at or before the age of seven years using the UK Millennium Cohort Study (MCS). Methods: Participants were born between 2000–2001 and recruited at 9 months, the first wave of the MCS, and subsequently participated in waves 2, 3 and 4 when they were three, five and seven years respectively. The study cohort consisted of singleton children, where the mother was the main respondent at the first wave and participated in the fourth wave at age seven years. HDP were self-reported by mothers at the first wave, where women were asked whether they had gestational hypertension, chronic hypertension, pre-eclampsia or eclampsia. The primary outcome was parent-reported diagnosis of asthma, based on responses to the International Study of Asthma and Allergies in Childhood (ISAAC) core questionnaire at age seven years. Crude and adjusted logistic regression models were used for data analysis. We adjusted for a range of potential confounders including socio-demographics (e.g. ethnicity, maternal age), obstetric factors (e.g. preterm delivery, parity), and established risk factors for asthma (e.g. parental smoking, family history of asthma, exposure to pollution). Moreover, we examined the risk of asthma among small for gestational age (SGA) children who were exposed to HDP compared to children not exposed to HDP. Results: At the first wave, 18, 818 children were recruited and13, 061 (69%) participated in the fourth wave at age seven years and were included in the analysis. 984 women (8%) reported having HDP and 2151 (16%) of the children had developed asthma by age seven years. In the crude logistic model HDP was significantly associated with asthma (OR=1.37; (95% CI: 1.17–1.61)) and the association was almost unchanged in the adjusted model (OR=1.39; (95% CI: 1.15–1.68)). This association was further strengthened in relation to HDP and SGA (Adjusted OR=1.60; (95% CI: 1.06–2.29). Conclusion: This study suggests that HDP exposure may increase the risk of asthma in the offspring and the association was independent of several potential confounders. Considering that the association was larger in relation to HDP/SGA compared to HDP alone, placental pathology may be a common factor increasing the risk of asthma.